THE EFFECT OF LEARNING MOTIVATION, SELF-CONTROL AND CRITICAL THINKING ON STUDENTS’ LEARNING ACHIEVEMENT AT OFFICE ADMINISTRATION EDUCATION STUDY PROGRAM, UNIVERSITAS NEGERI SURABAYA - Siti Aliva Mustikarini; Durinda Puspasari (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to analyze the effect of learning motivation, self-control, and critical thinking on students’ learning achievement at Office Administration Education study program, Universitas Negeri Surabaya. This study was quantitative research. The data were collected through questionnaires and interviews. The population in this study were students of the Office Administration Education study program, Universitas Negeri Surabaya, class of 2017, as many as 93 students. The samples in this study were selected through a total sample type, in which the number of samples were the same as the population, namely 93 students. Testing instruments in this study consisted of validity testing and reliability testing. The data analysis techniques used in this study were: 1) Classical assumptions consisting of normality test, multicollinearity test, and heteroscedasticity test; and 2) hypothesis testing using multiple linear regression. The results showed that: 1) there was a significant effect of learning motivation on the students’ learning achievement at Office Administration Education study program, Universitas Negeri Surabaya; 2) there was a significant effect of self-control on the students’ learning achievement at Office Administration Education study program, Universitas Negeri Surabaya; 3) there was a significant effect of critical thinking on the students’ learning achievement at Office Administration Education study program, Universitas Negeri Surabaya; and 4) there was a significant effect of learning motivation, self-control and critical thinking on the students’ learning achievement at Office Administration Education study program, Universitas Negeri Surabaya.